PERANCANGAN DAN IMPLEMENTASI SISTEM PEMBAYARAN KOMITE TERINTEGRASI GUNA AKSES PENGAMBILAN KEPUTUSAN TERKAIT DENGAN TRANSPARANSI PENGGUNAAN DANA PADA SMKN 3 SORONG PROVINSI PAPUA BARAT - Kasmy Edy; Markus Dwiyanto Tobi (LPPM Poltek ST Paul, 2020)
The financial payment system and school committee at SMK Negeri 3 Sorong are currently still conventional by recording on several payment cards then the payment data is recapitulated manually in a financial record book manually. This system takes a long time to process and has a large error rate. Besides, the speed of data access (reports), if needed, becomes too late, so that the speed of access to decision making is also hampered. This system should be replaced by using an integrated financial information system. This system can be accessed publicly via the internet network, so it is hoped that this system can facilitate the work of financial accounting and reporting. This research has the main objective of building an integrated financial information system, so it is hoped that this system will maximize the work of financial officers. The result of this research is an integrated payment application system product that will benefit the SMK Negeri 3 school institution. This study uses the RnD research method, in developing software adopting the waterfall method with the stages of planning, analysis, design, implementation, maintenance. Data collection methods in this research are observation and interview methods. This application was developed using PHP and Mysql. This payment information system provides facilities that can be used by users including data input, data search, and student payment reports, as well as real-time monitoring by homeroom teachers and school stakeholders.